A Hybrid Decision Support Model for Deploying Humanitarian Operations to Respond to Earthquakes. Issue 4 (2nd October 2022) - Geng, Shaoqing; Hou, Hanping; Yang, Jianliang
Abstract: This paper addresses the four essential humanitarian operations: location of emergency facilities, prepositioning of supplies, evacuation, and relief distribution by proposing a hybrid method that combines fuzzy set theory, analytic hierarchy process (AHP), a technique for order preference by similarity to an ideal solution (TOPSIS), and multi-objective programming. The objectives of the proposition are to minimize the evacuation distance, the cost of humanitarian operations, and the suitability of facilities based on qualitative factors while considering the demand, capacity, budget, and utilization constraints. Engineering managers can benefit from the collective expertise of multiple decision-makers, using their knowledge to automatically determine emergency facility location and allocation processes by running the proposed model. The model attempts to achieve a compromise solution for multiple objectives in various humanitarian operations. Finally, the real case study of the Wenchuan earthquake in China is taken to validate the model.